Malnutrition among under-five children in Nepal: A focus on socioeconomic status and maternal BMI - Jyoti Vijay; Kamalesh Kumar Patel (Elsevier, 2024)
Introduction: Malnutrition stands as the primary contributor to morbidity and mortality in children under the age of five. Nepal, situated in South Asia and classified as a low-income country, grapples with a significant malnutrition challenge. The elevated rates of malnutrition in Nepal are further compounded by its unfavorable socio-economic conditions, limited access to healthcare, poor maternal nutritional status, food insecurity, poor hygienic conditions, and geographical challenges. The consequences of mortality and illness associated with malnutrition directly undermine human capital and economic productivity. The main aim of the study is to determine the risk factors associated with stunting, underweight and wasting among under five children in Nepal. Subjects & methods: Nepal Demographic and Health Survey 2016 (NDHS) data was used for the study. The outcome measures were stunting, underweight and wasting. Predictor variables were categorized as mother, child and household related factors. The association between malnutrition and predictor variables were assessed by multivariate logistic regression using Stata 16.0 software and odds ratio (OR) with 95% confidence interval was reported. Results: A total of 2381 children under five years were included in this study for analysis. The magnitude of stunting (36%) was higher than underweight (27%) and wasting (10%) among under five children. Children from middle and rich households were 49% (OR = 0.51; 95%CI = 0.37-0.71) and 47% (OR = 0.53; 95%CI = 0.36-0.74) less risk of being stunted than children from poorest households. The odds of a child to be stunted was 1.6 times higher in those children living with 3-4 children than children with 1-2 children in their families (OR = 1.6; 95%CI = 1.24-2.07). Mother's BMI in category of normal (OR = 0.56; 95%CI 0.42-0.75) and overweight (OR = 0.30; 95%CI = 0.19-0.47) and larger birth spacing (OR = 0.53; 95%CI 0.36-0.74) were significantly associated with underweight and stunting among children, respectively. Conclusion: In Nepal, the problem of malnutrition among under five children is still high (36% of stunting and 10% of wasting). The study suggests that target-based approach and interventions should be administered for children from socio-economically deprived areas. Strategies should focus on preconceptions and the mother's nutritional status.